Incubators Within University And Clustered Contexts: Cases Of National Chiao Tung University (Nctu) And National Tsing Hua University (Nthu) Incubators In Hsinchu, Taiwan - Adham, Khairul Akmaliah (Asian Academy of Management (AAM), 2008)
Research literature on business incubators has highlighted the significance of clustered locational contexts and networking as key to an incubator's success. Using the case study approach, this study aimed to test the validity of this framework for explaining the level of success of the National Chiao Tung University (NCTU) and National Tsing Hua University (NTHU) Incubators in Hsinchu, Taiwan – both of which are highly-networked, cluster-centric and university-based. In-depth interviews were conducted with the managers of both incubators, and these were followed by information gathering on university patents and knowledge transfers from the research and development (R&D) office at each university. Analysis found that the incubators' locational contexts determined the degree and manner of their networking, but their profitability and growth potential were influenced by many other factors working in combination. Satisfying their sponsors' requirements and serving their core functions through sound management and strategic planning appeared to be the key to achieving profitability and sustainability, with benefits for all stakeholders. These constructs provide directions for more research on the performance of incubators and other business entities that are located within university and clustered contexts.